2021
DOI: 10.3389/fpls.2021.773090
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome-Scale Genome Assembly for Chinese Sour Jujube and Insights Into Its Genome Evolution and Domestication Signature

Abstract: Sour or wild jujube fruits and dried seeds are popular food all over the world. In this study, we reported a high-quality genome assembly of sour jujube (Ziziphus jujuba Mill. var. spinosa), with a size of 406 Mbp and scaffold N50 of 30.3 Mbp, which experienced only γ hexaploidization event, without recent genome duplication. Population structure analysis identified four jujube subgroups (two domesticated ones, i.e., D1 in West China and D2 in East/SouthEast China, semi-wild, and wild), which underwent an evol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 74 publications
0
15
0
Order By: Relevance
“…A total of 17 BURP genes were identified in 'Junzao' genome, and the variation of length of these sequences suggested high complexity within the ZjBURP gene family, as also reported in Medicago [35]. In addition, the genome sequences of 'Dongzao' and 'Wild jujube' have also been reported recently [36,37]; therefore, we can obtain more insight into the synteny and evolution of BURP gene family among wild, fresh, and dry jujube. Moreover, the chromosomal location of ZjBURPs in 'Junzao' genome may also provide clues for the formation and evolution of this gene family in jujube.…”
Section: Discussionmentioning
confidence: 57%
“…A total of 17 BURP genes were identified in 'Junzao' genome, and the variation of length of these sequences suggested high complexity within the ZjBURP gene family, as also reported in Medicago [35]. In addition, the genome sequences of 'Dongzao' and 'Wild jujube' have also been reported recently [36,37]; therefore, we can obtain more insight into the synteny and evolution of BURP gene family among wild, fresh, and dry jujube. Moreover, the chromosomal location of ZjBURPs in 'Junzao' genome may also provide clues for the formation and evolution of this gene family in jujube.…”
Section: Discussionmentioning
confidence: 57%
“…Mining additional genomic data for LOG mutations co-occurring with losses of prickles in other eudicot lineages, we found that the fruit-bearing tree crop jujube, commonly known as Chinese date (Ziziphus jujuba), in the Rhamnaceae family, carried two independent mutations (a 1 bp deletion and an exonic insertion) in a LOG homolog in two cultivars with suppressed prickles (also known as stipular spines) (Fig. 4B) (17)(18)(19). Importantly, neither mutation was found in Sour jujube (Z. jujuba var.…”
Section: Repeated Co-option Of Log Homologs Underlies Prickle Converg...mentioning
confidence: 99%
“…So far four versions of the genome assembly of jujube, including Z. jujuba ‘Dongzao’ [ 14 , 15 ] (DZV1, DZV2), Z. jujuba ‘Junzao’ [ 4 ] (JZV1) and Z. jujuba var. spinosa ‘Suanzao’ [ 16 ] (SJV1), has been achieved. These reported draft jujube genomes still contain a large number of unclosed gaps and fragmented unanchored sequences [ 4 , 14 , 16 ].…”
Section: Introductionmentioning
confidence: 99%